Pelaksanaan Perjanjian Kemitraan Antara Pengemudi Dengan Penyedia Layanan Grab : (Studi Di Kota Mataram) - Baiq Fuzira Ningsih; H. Salim Salim (Fakultas Hukum Universitas Mataram, 2022)
This study aims to identify and understand the implementation of the agreement and the settlement in the event of a dispute arising in the partnership agreement between the driver and the Grab service provider in the city of Mataram. The results of the study indicate that the partnership agreement in general has fulfilled the elements of the legal requirements of an agreement. The partnership agreement is officially formed when the driver-partner receives an SMS notification received from Grab. Disputes that occur between driver partners and Grab service providers are resolved through deliberation and if a settlement has not been found, it will be transferred to the Indonesian National Arbitration Board (BANI) and the decision issued is final.